Sensitivitas dan spesifisitas kartu menuju sehat model tikar monitoring pertumbuhan dalam mendeteksi stunting pada balita - Alfridsyah Alfridsyah; Ichsan Ichsan (AcTion: Aceh Nutrition Journal, 2022)
One of the obstacles faced in determining the diagnosis of stunting is the complexity and lack of accuracy of health workers, especially Integrated Healthcare Center (called Posyandu) cadres, in using current equipment (microtoice) and the lack of accuracy of nutrition workers in interpreting nutritional status.  The purpose of the study was to measure the validity of the KMS Tikar through sensitivity and specificity testing in detecting stunting in toddlers. The study used a Research & Development design, with the gold standard using a body length board and Z-Score calculation from 2005 WHO reference standard, carried out in 30 clusters in Darul Imarah District, Aceh Besar, from April to October 2019, and a sample of all children aged 0-24 months which is as many as 204 children. Data was collected through anthropometric measurements such as length and age and z-score data on the HAZ index. The WHO Anthro processed the data. The analysis was carried out with the Se and Sp tests. The results showed that children's body length measurement with both tools (Gold standard and growth chart is a mat model) had 0,073 cm. At the same time, the proportion of nutritional status in the stunting category was more commonly found in measurements using growth charts of mats (23,5%) compared to Gold Standards (12, 3%). The validity test results obtained a very high sensitivity value (100%) with a specificity of—87,15%. While the positive predictive value is 52,08%, and the negative predictive value is 100%. In conclusion, the growth monitoring mat growth chart has high sensitivity and specificity value and is very good for use as a tool to detect stunting in children aged 0-24 months.